Theoretical study on the charge transport in single crystals of TCNQ, F2-TCNQ and F4-TCNQ. Issue 5 (19th January 2018) - Ji, Li-Fei; Fan, Jian-Xun; Zhang, Shou-Feng; Ren, Ai-Min
Abstract : The outstanding electron transport behavior of F2 -TCNQ arises from its 3D close-packing motif and the nuclear tunneling effect; meanwhile, the poor transport properties of TCNQ and F4 -TCNQ stem from their poor packing and strong thermal disorder. Abstract : 2, 5-Difluoro-7, 7, 8, 8-tetracyanoquinodimethane (F2 -TCNQ) was recently reported to display excellent electron transport properties in single crystal field-effect transistors (FETs). Its carrier mobility can reach 25 cm 2 V −1 s −1 in devices. However, its counterparts TCNQ and F4 -TCNQ (tetrafluoro-7, 7, 8, 8-tetracyanoquinodimethane) do not exhibit the same highly efficient behavior. To better understand this significant difference in charge carrier mobility, a multiscale approach combining semiclassical Marcus hopping theory, a quantum nuclear enabled hopping model and molecular dynamics simulations was performed to assess the electron mobilities of the F n -TCNQ ( n = 0, 2, 4) systems in this work. The results indicated that the outstanding electron transport behavior of F2 -TCNQ arises from its effective 3D charge carrier percolation network due to its special packing motif and the nuclear tunneling effect. Moreover, the poor transport properties of TCNQ and F4 -TCNQ stem from their invalid packing and strong thermal disorder. It was found that Marcus theory underestimated the mobilities for all the systems, while the quantum model with the nuclear tunneling effect provided reasonable results compared to experiments. Moreover, the band-like transport behavior of F2 -TCNQ was well described by the quantum nuclear enabled hopping model. In addition, quantum theory of atoms in molecules (QTAIM) analysis and symmetry-adapted perturbation theory (SAPT) were used to characterize the intermolecular interactions in TCNQ, F2 -TCNQ and F4 -TCNQ crystals. A primary understanding of various noncovalent interaction responses for crystal formation is crucial to understand the structure–property relationships in organic molecular materials.